Manajemen Rumah Sakit dalam Kesiapsiagaan Menghadapi Bencana di RSUD Balaraja: Metode Hospital Safety Index - Nisaa, Puspita Gaharu; Modjo, Robiana (UI Scholars Hub, 2024)
Hospitals are required to provide health services under disaster conditions, serving as the front line to help survivors and patients. RSUD Balaraja of Tangerang Regency, the only Type B hospital owned by the Regency Government, is exposed to high potential disaster hazards, including floods, extreme waves, abrasions and tsunamis, as well as moderate risk of earthquakes. This study aims to analyse hospital management in disaster preparedness using a cross-sectional design with quantitative and qualitative approaches through Module 4 of the Hospital Safety Index and a phenomenological approach. The results showed that hospital management was rated as moderately safe in disaster preparedness, but other essential services were at high risk and required immediate improvement. The hospital's preparedness to protect patients and staff during and after disasters is still inadequate, particularly in terms of disaster management coordination, recovery planning and continuity of essential clinical services. Recommendations were made to improve disaster preparedness planning, procedures for agreements with external parties, sufficient budget and staff training. Keywords: disaster safe hospital, occupational safety and health, hospital, hospital management, management disaster.